Biology : An Australian Focus - Ladiges, Pauline [et al.] (North Ryde, N.S.W. McGraw Hill Australia, 2008)
This text refers to our unique Australian flora and fauna to illustrate principles of biology. Each copy of the text comes with a free CD-ROm of images and student resources. Authors Ladiges and Evans from Melbourne University, author Saint from ANU, ACT.
Include Glossary and Index
Keywords: Biology -- Biology--Study and teaching (Secondary)